ответ:
х₁= х₂=
пошаговое объяснение:
-x²+2х+1=1/х
-х+2х+1=1/х, х≠0
х+1=
(x+1)*x-1=0
+x-1=0
x=[tex]\frac{-1+-\sqrt{5} }{2}[/tex]
x= ,x≠0
x=
х₁=
х₂=
ответ:
х₁=
х₂=![\frac{-1+\sqrt{5} }{2}](/tex.php?f=\frac{-1+\sqrt{5} }{2})
пошаговое объяснение:
-x²+2х+1=1/х
-х+2х+1=1/х, х≠0
х+1=![\frac{1}{x}](/tex.php?f=\frac{1}{x})
(x+1)*x-1=0
x=[tex]\frac{-1+-\sqrt{5}
}{2}[/tex]
x=
,x≠0
x=![\frac{-1-\sqrt{5} }{2}](/tex.php?f=\frac{-1-\sqrt{5} }{2})
х₁=![\frac{-1-\sqrt{5} }{2}](/tex.php?f=\frac{-1-\sqrt{5} }{2})
х₂=![\frac{-1+\sqrt{5} }{2}](/tex.php?f=\frac{-1+\sqrt{5} }{2})